The Usage of Face Threatening Act in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement Movies - FIONA NASUTION, ANGGI (Language Horizon: Journal of Language Studies, 2013)
Abstrak Dalam interaksi, ada situasi dimana wajah seseorang kemungkinan akan terancam. Ucapan-ucapan yang mengganggu keseimbangan pemeliharaan wajah disebut Face Threatening Act (FTA). Penelitian ini dibuat berdasarkan studi Pragmatik. Tujuan penelitian ini adalah untuk memberikan gambaran tentang prinsip kesantunan, untuk menggambarkan dan menjelaskan jenis dan fungsi Face Threatening Act yang berkaitan dengan kesopanan di dalam percakapan oleh karakter dalam film Princess Diaries 1 dan Princess Diaries 2: The Royal Engagement. Ucapan-ucapan lisan yang muncul dalam film dianalisis dan diinterpretasikan secara deskriptif berdasarkan teori Face Threatening Act oleh Brown dan Levinson. Penelitian ini menggunakan metode deskriptif kualitatif. Data diambil dari dialog-dialog yang ada di dalam film Princess Diaries 1 dan Princess Diaries 2: The Royal Engagement, yang mengandung FTA pada karakter. Untuk mengumpulkan data, peneliti menggunakan beberapa langkah; mengumpulkan percakapan semua karakter dari kedua film dengan menontonnya dan mendengarkan percakapan dengan hati-hati, menggunakan medan catatan atau dokumentasi. Akhirnya, hasil penelitian menunjukkan bahwa ada dua macam FTA yang digunakan oleh karakter, yaitu positif FTA dan negatif FTA. Setiap jenis FTA memiliki efek berbahaya bagi pembicara dan pendengar/penerima. Ada juga lima macam strategi kesantunan, yaitu bald on-record, positive politeness, negative politeness, off-record dan do not do the FTA. Sebelum menjadi seorang putri, penggunaan positif FTA oleh Mia diterapkan untuk menunjukkan solidaritas untuk mendapatkan perhatian dan kepedulian dari teman-temannya di sekolah, karena bisa dibilang Mia berada di sosialisasi yang rendah diantara teman-temannya. Selain itu, penggunaan negatif FTA diterapkan dalam kasus-kasus khusus, seperti konteks "di dalam keluarganya" dan ketika dia belum mengetahui bahwa dia adalah seorang putri. Setelah menjadi seorang putri, Mia lebih sering menggunakan positif FTA saat berinteraksi dengan lawan bicara. Positif FTA diterapkan ketika dia ingin menunjukkan solidaritasnya untuk mendapatkan kesan yang baik dari masyarakatnya. Negatif FTA diterapkan hanya ketika dia dihadapkan pada orang karibnya. Penelitian ini diharapkan akan berguna bagi para peneliti selanjutnya yang tertarik dalam mempelajari FTA. Mereka bisa menganalisanya dari sudut pandang yang berbeda dan dari sumber data lain seperti drama dan novel. Kata Kunci: Kesantunan, wajah, face-threatening act Abstract In interaction, there are situations where someone’s face is likely to be threatened. Utterances that disrupt the balance of face maintenance are called Face Threatening Acts (FTAs). The research is based on Pragmatics study. The aims of the research are to give an overview of the politeness principles, to describe and to explain the types and functions of Face Threatening Act uses in relation with politeness in the conversation by the characters in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies. The oral utterances that appear in the movie are analyzed and interpreted descriptively based on Brown and Levinson’s Face Threatening Acts theory. This research employs descriptive qualitative method. The data are taken from the dialogs in the film entitled Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies, that contain FTA that used by characters. To collect the data, the researcher uses some steps; collecting the conversation of all the characters in those movies by watching it and listening the conversations carefully, uses fields note or documentation. Finally, the result of the research shows that there are two kinds of FTA that used by the characters, namely negative FTA and positive FTA. Each type of FTA has harmful effects for the speaker and the hearer/receiver. There are also five kinds of politeness strategy, they are bald on-record, positive politeness, negative politeness, off-record and do not do the FTA. Before becoming a princess, the use of positive FTA by Mia is applied to show solidarity in order to get attention and care from her friends at school, since she arguably is in lower socialization. Moreover, the use of negative FTA is applied in a special cases, such as “inside her family” context and when she has not known yet that she is a princess. After becoming a princess, Mia is more often using positive FTA when interacting with her interlocutor. Positive FTA is applied when she wants to show her solidarity in order to get a good impression from her people. Negative FTA is applied only when she faced in her closest people. Hopefully, this research will be useful for future researchers who are interested in studying FTA. They can analyze it from a different point of view and from other data source such as drama and novel. KEY WORDS: politeness, face, face-threatening act. INTRODUCTION Communication is one of the most important matters for living things, especially for human. In this society, human beings need to cooperate with other people around them. They cannot live alone. They have to communicate in order to help them fulfill their needs, because they cannot get what they want if they do not say it. So that, they need language to communicate each other in order to share, support their own identity, build social contact, and influence others to feel, think, and have an action as they want. And also, they can offer something, refuse something, and show what in their mind in spoken and written forms. Besides, the use of politeness is also important, because people cannot utter any utterance without looking for their addressee. According to Yule (2006:119), language is a reflection of culture and accepted cultural norms, polite conducted and interactions inseparable to culture. Polite interaction takes on many forms in the way people interact, not only by the spoken word but also by the unspoken messages portrayed by behavior, body language, eye contact and facial expressions. Politeness is a fundamental part of culture which shapes human behavior within a society. According to Goode (2000:25), he explains that: “this politeness and behavior as an ‘integrated pattern of human behavior that includes thoughts, communications, languages, practices, beliefs, values, customs, courtesies, rituals, manners of interacting and roles, relationships and expected behaviors of a racial, ethnic, religious or social group; and the ability to transmit the above to succeed generations.” This view illustrates the importance of politeness in language teaching, culture and politeness is mirrored and represented in all the above human interactions. A face-threatening (FTA) is an act which challenges the face wants of an interlocutor. According to Brown and Levinson (1987:25), face-threatening acts may threaten either the speaker’s face or the hearer’s face, and they may threaten either positive face or negative face. Every single thing we dare to say will affect not only our hearer’s face but also our own face. The researcher chooses Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movie since those movies tell about a royal’s life as a theme. It can be seen clearly from the title and all of us know that something which refers to such a royal story has a deep connection with politeness. The researcher analyzes both serial movies, because of their story itself. The first sequel tells about a socially awkward but very bright 15-year-old girl, Mia Thermopolis, who is being raised by a single mom, discovers that she is the princess of a small European country, because of the recent death of her father, who, unknown to her, was the crown prince of Genovia. Suddenly, Mia’s life is thrown into complete overload. She is being taught about scarves, waves and pears in order to become a perfect princess, she gets a makeover and bodyguard/limo driver called Joe. On top of all that Mia has a choice between continuing the life of a San Fransisco teenager and stepping up to the throne. Based on the story, we can imagine that Mia, who has a normal life in the beginning episode, has to maintain her image since she knows that she is actually a princess. The usage of FTA appears many times unconciously in her daily life in the way she talks with her mom, friends, even her grandma who is a queen; she could not manage her image yet. But it is not only Mia who applies FTA here, but the other characters like the society, teachers, and so on apply FTA too. However in the second movie, Mia Thermopolis is now a college graduate and on her way to Genovia to take up her duties as a princess. Her best friend, Lily, also joins her for the summer. Mia continues her 'princess lessons'- riding horses side-saddle, archery, and other royal. But her complicated life is turned upside down once again when she does not only learn that she has to take the crown as queen earlier than expected, but also she has to be married before this event. From that moment it can be seen that Mia now lives in a royal society and now she has known with whom she talks with to maintain her image as a princess and manage her politeness. So it can be imagined too how the characters used the language in their conversation inside in a palace. How they apply their FTA in different contexts. Besides, the language used is easy to understand. The researcher aims are to give an overview of the politeness principles, and to tell the readers what FTA is actually and how important to manage a FTA in our daily life based on Brown and Levinson’s theory. From the description on the background above, it is considered very necessary to do an action research to solve the problems, like (1) What are the types of Face-threatening Act used by the characters in the movie? (2) What are the functions of each Face-threatening Act which are used by the characters in the movie? And (3) In what context do the characters use a Face-threatening Act for politeness strategy? The results of this study are expected to provide practical and theoretical benefit for life and linguistic development in general and pragmatics in particular. Practical benefit is closely related to various development efforts in various areas of politeness studies, one of that is movie. In the Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies, they are presenting the meaning of Face Threatening Act as a politeness theory. The researcher also expects that the results of this study can be used as inputs to them; other students and those serving in the field of FTA in order their knowledge become more complete and in-depth. The theoretical benefit of this research is to help explain aspects of the language that cannot be reached by the description of syntax, morphology, phonology and semantics in linguistic studies. In addition it is hoped that this study could enrich the literature pragmatic of politeness, especially FTA. RESEARCH METHOD This research is classified as a descriptive qualitative method because the data of this research are in the form of utterances and words which are not statistically analyzed and do not deal with number at all. Beside of that, the descriptive qualitative method is used because the aims of this research are to describe and to explain the types and functions of Face Threatening Act uses in relation with politeness in the conversation by all of the characters in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies. The oral utterances that appear in the movie are analyzed and interpreted descriptively based on Brown and Levinson’s Face Threatening Acts theory. The data of this research are taken from the conversations by all of the characters in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movie. There are many interesting news that are found in its section (words, phrases or sentences) which contain politeness strategy including in it, the Face Threatening Act itself. Therefore, it can attract and persuade the reader’s attention directly to know more about it. In this research, the data are gathered from the utterances or words in the conversations by all of the characters in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies. The technique that is used for this research is Non Participant Observation Technique. Non Participant Observation is a research technique whereby the researcher watches the subjects of his/her study, with their knowledge, but without taking an active part in the situation (http://www.ask.com/question/what-is-non-participant-observation). It is a simple method to use because the data are collected by observing behavior without interacting with the participants. So, it is easier for the researcher to record data promptly and objectively, like a movie, as one of the example.To collect the data, the researcher uses two steps: (1) Collecting the conversation of all the characters in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies by watching the movie and listening the conversations carefully in order to get deep understanding about the topic, and (2) Because this research intends to qualitative study, in collecting the data, the researcher applies fields note or documentation. Then, the researcher selects the data obtained from data sources to meet the nature of the problems of the study. For the instruments, the researcher uses the both movies, Princess Diaries 1 and Princess Diaries 2: The Royal Engagement, paper and pen. The first step in analyzing the data is collecting the data. After getting the data from the conversation between each other of all the characters in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies, then the researcher analyze the data. To analyze the data, there are several steps: first, the researcher here starts to divide the analysis into four scopes; Mia as a speaker before becoming a princess, Mia as a hearer before becoming a princess, Mia as a speaker after becoming a princess, and Mia as a hearer after becoming a princess. After that, the researcher analyzes the types of face-threatening acts that appeared by each character in Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies. After finding the types, the researcher starts to find out the functions of politeness strategy especially Face Threatening Act by Brown and Levinson theory on each type and the interpretation of reference them. The last step, the researcher tries to describe the context in which characters use Face Threatening Act for politeness strategy. POLITENESS THEORY Politeness in any given society is conducted within a system of acceptable social behaviour and social linguistic cultural norms that govern the way in which citizens interact. Interacting and communicating are fundamental parts of life -from catching a bus, greeting a neighbour to business transactions- and are conducted by following social and sociolinguistic accepted norms. ‘Language is the principle means whereby we conduct our social lives. When it is used in contexts of communication, it is bound up with culture in multiple and complex ways’ (Kramsch, 1998:89). Politeness theory is the theory that accounts for the redressing of the affronts to face posed by face-threatening acts to addressee. First formulated in 1987 by Penelope Brown and Stephen Levinson, politeness theory has since expanded academia’s perception of politeness. Politeness is the expression of the speakers’ intention to mitigate face threats carried by certain face threatening acts toward another (Mills, 2003, p. 6). Another definition is a battery of social skills whose goal is to ensure everyone feels affirmed in a social interaction. Being polite therefore consists of attempting to save face for another. Positive and negative face Face is the public self-image that every adult tries to project. In their 1987 book, Brown and Levinson defined positive face two ways: The want of every member that his wants be desirable to at least some others executors, or alternately, the positive consistent self-image or 'personality' (crucially including the desire that this self-image be appreciated and approved of) claimed by interactants. Negative face was defined as "the want of every 'competent adult member' that his actions be unimpeded by others", or "the basic claim to territories, personal preserves, rights to non-distraction--i.e. the freedom of action and freedom from imposition". At the same time, he characterized negative face by the desire not to be imposed upon, noting that negative face could be impinged upon by imposing on someone. Ten years later, Brown characterized positive face by desires to be liked, admired, ratified, and related to positively, noting that one would threaten positive face by ignoring someone. Positive Face refers to one's self-esteem, while negative face refers to one's freedom to act. The two aspects of face are the basic wants in any social interaction, and so during any social interaction, cooperation is needed amongst the participants to maintain each other's faces. FACE THREATENING ACT Face-threatening acts are acts which in some way threaten the 'face' or self-esteem of another person. Some people think that all communicative acts are potentially threatening. In fact, the potential does exist to threaten 'face' with every act of communication. Whether the act is actually a threat depends not so much on the intent of the speaker but on the perception of the hearer. Face-threatening Acts include acts other than spoken or written. Very often we can threaten others' face by a look, an expression or some other non-verbal communication. Staring at someone is often perceived as a FTA for no other reason than it can be so unnerving. The starrer’s motivation is always questioned. The person who is being stared at must wonder, what is wrong. A child (or adult) at times can be more expressive and rather than hide a FTA, might express him or herself openly. Sticking one's tongue out at someone else can be done with no attempt to conceal the act. It can be an FTA 'in your face' (Leech, 1983:56). Negative face-threatening acts Negative face is threatened when an individual does not avoid or intend to avoid the obstruction of their interlocutor's freedom of action. It can cause damage to either the speaker or the hearer, and makes one of the interlocutors submit their will to the other. Freedom of choice and action are impeded when negative face is threatened. Damage to the hearer An act that affirms or denies a future act of the hearer creates pressure on the hearer to either perform or not perform the act. Examples: orders, requests, suggestions, advice, reminding, threats, or warnings. Damage to the speaker An act that shows that the speaker is succumbing to the power of the hearer. Examples: expressing thanks, excuses, accepting a thank you or apology, acceptance of offers. Positive face-threatening acts Positive face is threatened when the speaker or hearer does not care about their interactor’s feelings, wants, or does not want what the other wants. Positive face threatening acts can also cause damage to the speaker or the hearer. When an individual is forced to be separated from others so that their well-being is treated less importantly, positive face is threatened. Damage to the hearer An act that expresses the speaker’s negative assessment of the hearer’s positive face or an element of his/her positive face. The speaker can display this disapproval in two ways. The first approach is for the speaker to directly or indirectly indicate that he dislikes some aspect of the hearer’s possessions, desires, or personal attributes. The second approach is for the speaker to express disapproval by stating or implying that the hearer is wrong, irrational, or misguided. Examples: expressions of disapproval (e.g. insults, accusations, complaints), contradictions, disagreements, or challenges. Damage to the speaker An act that shows that the speaker is in some sense wrong, and unable to control himself. Examples: apologies, acceptance of a compliment, etc. POLITENESS STRATEGIES WITH FTA Bald On-Record Bald on record is not attempting to minimize the face threat. Bald on-record strategies usually do not attempt to minimize the threat to the hearer’s face, although there are ways that bald on-record politeness can be used in trying to minimize face-threatening acts implicitly. Often using such a strategy will shock or embarrass the hearer, and so this strategy is most often utilized in situations where the speaker has a close relationship with the audience, such as family or close friends. To respond to a face threatening act, bald on record is to reply bluntly and often rudely. This could be done by treating the face of the other person. For example, if someone commits a face threatening act by telling you to 'Shut up' and that they do not care about your story, a bald on record reply may be to tell them that you did not want to talk to them anyway, or no, you will not shut up. Bald on record responses are often aggressive. Positive Politeness Positive politeness is showing you value someone so minimizing the threat to the positive face. Positive politeness is a theory put forward by Brown and Levinson. To be positively polite is to be inclusive of the other person, to make them feel although their opinion and companionship are both desired and valued. This is a way of addressing every persons need to feel wanted and appreciated. Positive politeness appeals to a person’s self-esteem rather than their freedoms as an individual. It is often over looked or not considered as a politeness strategy in English culture. An example of positive politeness may be to make sure that everyone is personally welcomed into a party, or asking someone’s opinion on what to do. Positive politeness strategies seek to minimize the threat to the hearer’s positive face. They are used to make the hearer feel good about himself, his interests or possessions, and are most usually used in situations where the audience knows each other fairly well. In addition to hedging and attempts to avoid conflict, some strategies of positive politeness include statements of friendship, solidarity, compliments, and the following examples from Brown and Levinson. Negative politeness Negative politeness is not impeding on someone so minimizing the threat to the negative face. Appealing to someone through negative politeness is respecting their personal space and not intruding on them. Trying to cause as little inconvenience as possible and apologizing if engaging which them are acts which represents negative politeness. For example, being negatively polite may be to ask someone if you may open a window, so as not to infringe on their desire to have it shut or to ask "It is not too much trouble, could you please open the window?". Therefore it is giving options. Negative politeness can even go as far as to not direct request something in fear of infringement, but rather to hint at your desire and hope the other person complies. For example; "is not it rather cold in here?" if you want the window to be shut. Negative politeness is when a face threatening act is minimized, the speaker is less imposing and preserving your own “negative face”. Negative politeness strategies are oriented towards the hearer’s negative face and emphasize avoidance of imposition on the hearer. These strategies presume that the speaker will be imposing on the hearer and there is a higher potential for awkwardness or embarrassment than in bald on record strategies and positive politeness strategies. Negative face is the desire to remain autonomous so the speaker is more apt to include an out for the hearer, through distancing styles like apologies. It is clearly a strategy for negative politeness and the redressing of a threat to negative face, through things like favour-seeking. Off-Record (indirect) The other politeness strategy outlined by Brown and Levinson is the indirect strategy. Off record is avoiding responsibility for the FTA often by being indirect. It means to response to a face-threatening act is to not response to it at all. This may mean completely ignoring the comment, or to comply with what the face-threatening act instructed you to do. This strategy uses indirect language and removes the speaker from the potential to be imposing. For example, a speaker is using the indirect strategy might merely say “wow, it is getting cold in here” insinuating that it would be nice if the hearer would get up and turn up the thermostat without directly asking the hearer to do so. Do Not Do the Face-Threatening Act This strategy involves several points. They are: (1) Speaker avoids offending the hearer at all (2) Speaker also fails to achieve his/her desired communication and (3) No overt examples exist MIA IN HER ROLE AS SPEAKER BEFORE BECOMING A PRINCESS The data is taken when the Music Class begins. Some students take their position, such as a choir, instrument players etc. Mia and Lily are included in the choir, while Michael, Lily’s brother, plays the piano part. When the teacher comes, the students who originally still relaxed, then stand occupy their position. Mia : Charles, you want to be in the front? Charles : Thanks. Mia : No problem. [Change positions each other]. Mia, who is initially located in the front row, suddenly makes a bid to Charles, who is behind her, to change the position. Utterance like 'Charles, you want to be in the front?’ indicates that Mia applies positive face. It can be said positive face because Mia shows her solidarity to share with Charles. Her positive face is a desire to be liked or appreciated by Charles. In data 1, Mia offers Charles a chance to change position if Charles does not like to be in the second row. Based on Brown and Levinson's theory, an offer qualifies as a FTA. With positive face, it means Mia is also applying positive FTA. Positive FTA which is implemented by Mia include dangerous for her face as a speaker, since the answer of Charles for Mia’s offer could be yes or not. However, because Charles agrees Mia’s bid, it means the danger of the speaker's face is actually very small because Charles is also willing to be on the front row and the act is clearly in the hearer's interest. While Charles, as a hearer, is responding Mia’s offer by saying 'thanks'. It means he applies the one of politeness strategies, positive politeness, on Mia's positive face for her kindness. Charles is using positive politeness strategy to minimize the sting of a FTA. The redressive action must be used for Charles to show that he wants Mia's wants. The context that is associated with this data is Mia’s conflict itself. Mia, who is feeling low among her friends, does not feel worthy to be in the front row. In her daily life, Mia has always been considered "invisible" by her friends. Mia feels that she does not deserve to be a leader in any activities, including standing in the front row in choir practice. Mia then gives a chance to her friend, in this case Charles, in order to get a good respect from the others, except Lily, her best friend of course. By showing her solidarity, indirectly Mia hopes her presence will be meaningful and have a place in the hearts of her friends. Charles’ thanks statement comforts Mia’s heart. Mia would rather be in the rear than in the front. The observation is impossible without knowledge of the politeness theory. In terms of politeness by Goode, both expressing politeness means. Mia gives an offer which is also wanted by Charles. It means that she shows decency by being nice to Charles and also avenges Charles’ gratitude as well. On the other hand, Charles thanks for Mia’s offer because he is happy for it. It was stated in Goode's book (2000:56), that one of the politeness functions is to be nice to each other to create social kinship. MIA IN HER ROLE AS HEARER BEFORE BECOMING A PRINCESS The data is taken when Mia and Clarisse go have fun alone together using Mia’s old car. Bus Driver : Put down destruction of public property. Officer : I will, I will. And last, but not least driving without a license, Accompanied by an adult whose license expired 45 years ago. Clarisse : I’ve been trying to tell you, officer. Licenses don’t expire in Genovia. Not for the Queen. Don’t I have diplomatic immunity? Officer : You do, but her we have to take downtown. [Pointing fiercely at Mia.] Mia : What? Officer : I’m sorry, Miss. Clarisse : It’s allright, officer. I understand. I... I understand perfectly. Mia : You do? Clarisse : Mia, no town, no city, no country, can function peacefully, if its officers and its transportation engineers don’t follow the letter of the law. Mia’s older car that makes this event deals with police officer. This incident occurred when road which is impassable, ride by them. Due to Mia’s old car, the engine is not strong enough to pass through a road that climbs up. Mia, as a driver, cannot control it so that hit a mini bus that is behind her. Soon the police officer comes with a mini bus driver who feels aggrieved. Clarisse put forward her complaint because Clarisse feels unworthy to being ticketed since she is a queen of the country. The police officer can understand it. But in the context of the above conversation, the police said his FTA to Mia because Mia is just ordinary people, ordinary teenager who is driving a car without a driving license. As a child who is still adapting to the fact that she is a princess, Mia cannot strategize her words in order to people to respect her. Actually, by saying out the words smoothly and wisdomly, can ease the emotional and heartbreaking of police, so that police officer does not want to ticketed her. Mia, who recognized that her face is threat by the officer, gives a statement in bald on-record by saying ‘What?’. Mia feels that it is not fear expressed her shocking reaction. Mia responds him by saying 'what?' like sound harshly, because Mia has not understood the manners and etiquette how to be a princess. It means that Mia applies negative FTA with bald on-record politeness strategy by Brown and Levinson’s. That is why the police apply the negative FTA on Mia. In Clarisse’s utterance, Clarisse shows that she is making complaint which means she is applying FTA to the officer. However, the officer gives Clarisse an agreement or the defense to her by saying 'you do'. It means that the officer applies positive politeness. But the next of his sentence, ‘but her we have to take downtown’ states that the chief officer applies negative FTA to Mia. The sentence that followed by pointing and seeing fiercely is truly as a FTA, especially negative FTA. The meaning of FTA’s officer is to remind that normal citizen deserves to get destiny as if she (Mia) disobey the traffic light. However, the officer still applies positive face because he is making apologize. MIA IN HER ROLE AS SPEAKER AFTER BECOMING A PRINCESS The data is taken when the event of royal road’s parade is coming. Mia : Carolina, would you like to be a princess today? Carolina : I can’t. I’m too little. Too piccola. Mia : Oh, no. Because I declare that anyone can be a princess today. Well, why don’t we get you a tiara and you can wave, and march in the parade? At that time, Mia sees Carolina, the orphan child, bullied by two male friends in her own age. Mia, who could not bear to see it, suddenly stops for coming near to Carolina and two young boys. In Mia's first utterance, 'Carolina, would you like to be a princess today?', it can be seen that Mia makes an offer to Carolina. The statement shows that Mia applies positive FTA which damage to the speaker. In the other hand, Carolina replies it directly. She immediately says no and explains her reason. So it can be said that Caroline has a negative face. However, in Mia's next utterance 'Oh, no.', shows Mia’s disapproval of Carolina’s statement. But Mia adds 'Because I declare that anyone can be a princess today.’ shows that she offers contrasting ideas. Like Reuscher's said "By putting forth a Differing ideas or offering an Opposing point of view, we challenge the other person's personal or emotional investment in what could be a deeply-held opinion". However, even though based on Reuscher’s theory the words of Mia are included in the FTA, but it is different according to George Yule. In his book he explains that Mia’s sentence is not included in the FTA. Mia legitimate uses meaningful utterance affirmation like "I declare", because Mia is a princess, who has a higher status than other people. Mia’s sentence shows solidarity/sympathy to the people especially children orphaned. Mia’s FTA treatment at Carolina actually contains its own context or reason. Mia does not bear to see a little girl, who looks weak, persecuted by her two friends. When looking at the incident, cursory Mia remembers about her past. Caroline’s incident reminds Mia in which she also has experienced the same thing. Before becoming a princess, Mia always scorned, mocked, persecuted, and even considered "invisible" by her friends (as in the data 11-14), because she looks ugly and messy. The feeling of sad by saying Carolina, makes Mia applies her positive FTA to Carolina. Mia’s instinct compels her to defend Carolina. As a princess now, Mia is seemed to take revenge. Mia does not want someone to have the same experience, let alone Carolina, as an orphan. For more entertaining Carolina, Mia even gives her a chance to join that parade in order to Carolina knows how it feels to become a princess. Mia does it because she understands Carolina’s sadness feeling. MIA IN HER ROLE AS HEARER AFTER BECOMING A PRINCESS The data is taken when Mia is in the barn after the side-saddle’s incident. Nicholas : You shouldn’t hide. It only makes them gossip more. Mia : What do you want? Nicholas : Just think, Mia. One more leg and you could’ve easily outrun your horse. Mia : I don’t need this right now. In doing so, Mia will feel pressure to have to agree or not to the Nicholas’ advice, since Mia, who has been hiding after the fatal incident. And on the side of Mia, Mia turns to bluntly responded, bald on-record. It means that Mia applies negative FTA that harmful to the hearer. Using such a strategy will shock or embarrass the hearer because it shows that she does not want to know or does not want to be blamed for what she had done. From her utterance, 'What do you want?', the function of the utterance is clear, unambiguous and concise. However, although clear and concise, this also carries a fair amount of risk. It is because to be blunt with someone indicates that you do not care about their face. However, even though Mia responds it by on-record, Nicholas still gives suggestion/advice on what is already happening. Mia, as the hearer, still responds with negative face, with bluntly again, no redressive action. It means that Mia makes Nicholas losts his face. We can see that Nicholas has a positive face in the first sentence, 'You should not hide'. Nicholas shows his empathy/solidarity about what happened to Mia. Nicholas is seen giving advice to Mia so as not to hide. Nicholas also adds to his sentence what the result is of Mia’s hiding actions. It is proved from his sentence, 'It only makes them gossip more'. Because of his concern by adding a sentence like that to remind Mia, then Nicholas has clearly considered positive face. But both Nicholas’ statement that implies giving advice, are the negative FTA which damage to the hearer/receiver. From the context of the conversation above, Nicholas gives advice to Mia in order to gets Mia’s heart. He comes to cheer Mia who is crying feel ashamed. On the side of Mia, Mia fells very ashamed of what happened to her. Mia is very shame that many of the officials who know that Mia actually cannot ride side-saddle. Therefore, Mia gets alone and cries alone in the barn. Here, Mia replies Nicholas’ advice roughly. Indeed, after becomes a princess, Mia is able to organize her words better toward anyone. However, toward Nicholas this time, Mia responds harshly, because Mia hates Nicholas, as her rival at the time. Mia, who knows that Nicholas is a man who wants to usurp her throne, considers the arrival of Nicholas is not the right thing for her. Mia fells that actually Nicholas laughs her and concludes that Mia does not deserve to be the leader of the kingdom. Mia is also being bad-mood at the time, so she does not want to hear advice from anyone, especially from Nicholas. It would be a beneficial challenge for the researcher to compare two different things from a source such as movie. Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movies, are prime examples of politeness theory in action. The FTA is a concept that noone who has not learned the politeness theory can easily understand. Doing FTA in the right way, can make us feel comfortable and more understand the deeper meaning of politeness. In the Princess Diaries 1 and Princess Diaries 2: The Royal Engagement movie, the researcher divides it into two parts, Mia as a speaker and Mia as a hearer, which also means that Mia gets FTA from her interlocutor. From the research that has been conducted by the researcher, there are two phases in the Princess Diaries 1 movie. The first phase is when Mia is a normal teenager, does not know yet that she is actually a princess. The second phase is when Mia has known that she is actually a princess. From the table that is shown in the findings, those ten data which are taken while Mia in her role as a speaker, the results show that Mia applies five positive and five negative FTA. Positive FTA is applied when Mia wants to be among her friends at school, with the offer, thanks and apology expressions. While her negative FTA is applied considering that Mia is still sloppy, does not understand how the way speaking with a good word. The point is that Mia has not had a soft personality yet before becoming a princess and has not been able to put the FTA as it should be. In her position as a hearer/receiver, Mia tends to reply the FTA she got by non-verbal action, such as smile only. That happens because Mia feels that she has no any authority or power to avenge the FTA from the people who insult her. Mia does not contradict or make excuses, but keep silent and smile at people who give insults or advice at her. Broadly concluded, before becoming a princess, Mia tends to apply positive FTA. This happened in the same condition when Mia as a speaker or as a hearer. Positive FTA is applied when Mia is in the social environment as a normal girl teenager who wants to have many friends. Mia wants to shows her solidarity and her concern in order to her friends want to be friends with her. But Mia also applies negative FTA. Negative FTA is applied in the context when Mia faces her closest people, like Helen and Clarisse. The points that are taken on Mia’s negative FTA are Mia-spoken way. With Helen, Mia used non formal words more often although Helen is her real mother. Due to the very close relationship, like a friend, so Mia does not feel afraid that she will hurt Helen when she applies a negative FTA in form of direct questions to her. Then with Clarisse, who is still perceived as a stranger at first, Mia does not hesitate to apply negative FTA because Mia does not feel to need the attention from her. Before becoming a princess, Mia is not able to manage her words well. In Princess Diaries 2: The Royal Engagement, after becoming a princess, Mia tends to use positive FTA when she roles as a speaker. It is because Mia who is already able to maintain her image as a princess with a well-spoken and understand with whom she speaks to. Meanwhile, when she is as the hearer, from 5 data taken, positive FTA is more often to be applied by Mia. Broadly concluded, after becoming a princess, Mia no longer lives in the neighborhood of ordinary people, but in a royal family environment. As a princess, Mia wants to get a good impression in the hearts of her people. Therefore, Mia is more likely applies positive FTA. And after becoming a princess, Mia could have been better in how to speak a kind word and a polite, not as shown in the first movie, when she has not been a princess yet. Mia is also able to understand her image as a princess better. In addition, Mia rarely applies negative FTA. Mia applies it only in certain contexts, like to Nicholas, who becomes her rival to fight over the throne as well as the people she loved. We have seen how FTA is performed. There are situations where someone’s face is likely to be threatened. The two aspects of face are the basic wants in any social interaction, and so during any social interaction, cooperation is needed amongst the participants to maintain each other’s faces. Subsequently, we see here that verbal interaction would become odd if FTAs are not part of language usage. It is because without FTAs, noone would ever complain, noone would ever ask someone to do something or ask questions (Simpson, 1997: 305). Therefore, we can say that FTAs are a necessary feature of interaction. CONCLUSION In line with the previous chapter, the conclusion of this research can be formulated based on the proposed research question. Before and after becoming a Princess, there are two types of face-threatening acts that are applied by Mia. They are positive face-threatening act and negative face-threatening act. Before becoming a princess, the function of positive FTA that is applied by Mia, is to show solidarity in order to get attention and care from her friends at school. But after she becomes a princess, the function is none other than she wants to show her solidarity in order to get a good impression from her people. Moreover, the function of negative FTA that is applied by Mia before and after she becomes a princess is to show negative expression, such as anger. The context that is associated with positive FTA of Mia before she becomes a princess, because she arguably is in lower socialization in her school. It is different with after she becomes a princess; she rules a country now and can maintain her image better. In the other hand, Mia has different context when she applies negative FTA, before and after she becomes a princess. Before becoming a princess, she does negative FTA in a special cases, such as “inside her family” context and when she has not known yet that she is a princess. While after becoming a princess, she only applies it when she faced her closest people, like Nicholas The theme in Princess Diaries 1 refers to the adaptation process of an ordinary Mia until she knows that she is a princess. But in Princess Diaries 2: The Royal Engagement movie, the theme refers more on the subject of Mia’s romance. Even so, the researcher is still taking the difference in the way Mia does FTA before and after being a princess. By looking at this analysis, it is hoped that we can learn how to implement the FTA in everyday life because FTA is very important in order to create a comfortable interaction with each other In addition, it is also recommended for the next researchers who are interested in doing further researches in this area to use these finding as a starting point in conducting the research. Using the same theory of Brown and Levinson, the next researchers are suggested to use different data sources, in this case daily conversation which can be formal or informal dialogue or in any literary work. The researchers should consider how a language uses influences the face-threatening act. To make this thesis more perfectly, the criticism and suggestion from the readers are needed. REFERENCES Brown, Penelope and Stephen C. Levinson. 1987. Politeness: Some Universal in Language Usage. Cambridge: Cambridge University Press. Coates, B. 1998. Discourse Analysis. Oxford: Blackwell. Gino, Johnstone. 2002. A Critique of Politeness Theory. Oxford: Teachers College Press. Goode, Swink. 2000. The Communication Functions of Politeness Theories. Chicago: Chicago Linguistics Society. Holmes, G.A. 1988. Thoughts and Utterances: The Pragmatics of Explicit Communication. Oxford: Blackwell. Kramsch, William. 1998. The Form of Linguistic and Relevance. Philadelphia: University of Pennsylvania Press. Leech, G.N. 1983. Principles of Pragmatics. New York: Longman. Miki, Murakami. 2011. Compensation for Face Threatening Act in Service Encounters in Japan and United States. Oregon: Portland State University. Mills, P. 2003. Approaches to Pragmatics. New York: MIT Press. Nall, Shu Pin. 2006. FTA Strategies Used in International Trade Email Correspondence. Taiwan: National Kimmen Institute of Technology. Reuscher, Smith. 2000. Politeness Distinction in Personal Pronouns and the Concept of Face. Oxford: Blackwell. Simpson, Michael. 1997. Doing Pragmatics in Society. New York: Longman. Yule, George. 2006. The Study of Language. Cambridge: Cambridge of University Press. Internet Source: http://www.ask.com/question/what-is-non-participant-observation (Retrieved on July 30th, 2013) http://en.wikipedia.org/wiki/The_Princess_Diaries_(film) (Retrieved on July 31st, 2013) http://en.wikipedia.org/wiki/The_Princess_Diaries_2:_Royal_Engagement (Retrieved on July 31st, 2013)